Arqueología cocreativa para la preservación del patrimonio cultural: experiencias desde Nivín, Casma, Perú - Cruzado, Elizabeth (2023)
New approaches and social dynamics are enabling the establishment of an essential connection between archaeologists and the community that allow us to understand the significance and legitimacy the past holds for modern communities. In this context, cultural heritage has the role of connecting and justifying the preservation of the past in order to give it a social use and imbue it with value for the community. The work underway at Nivín was based on these ideas, and had as its main goal establishing and strengthening the connection between cultural heritage and the local community through public archaeology with a co-creative approach. This means collaborating with the local people in accordance with their needs and concerns, in order to become allies in the pursuit of information and in the development of activities that integrate the past with the present. These collaborative practices between the local school and archaeologists took place through educational and artistic activities promoting the preservation, presentation, and interpretation of Nivín’s cultural heritage. This article explores the collaborative work carried out at Nivín, the interactions between its participants, the impact these efforts have on, and the dynamics of heritage preservation.